2022
DOI: 10.3390/rs14184626
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Climate Change and Human Activities on Vegetation Productivity Variation in National Nature Reserves on the Qinghai–Tibetan Plateau

Abstract: National nature reserves (NNRs) are at the forefront of conservation efforts on the Qinghai–Tibetan Plateau (QTP). However, few studies have examined the vegetation dynamics and their driving forces at the whole QTP scale. In this study, we used potential Net Primary Productivity (PNPP), actual NPP (ANPP), and human-activity-induced NPP (HNPP) to analyze the vegetation dynamics of 42 NNRs on the QTP. Further, we determined the driving factors of vegetation dynamics from 2000 to 2020. The results indicate that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…The descending order of these indices was PNPP, HNPP, and ANPP. This concurred with previous research [49,61,62] and indicated the efficacy of these indicators in analyzing the study area.…”
Section: Spatial and Temporal Distribution And Changing Trend Of Anppsupporting
confidence: 92%
See 3 more Smart Citations
“…The descending order of these indices was PNPP, HNPP, and ANPP. This concurred with previous research [49,61,62] and indicated the efficacy of these indicators in analyzing the study area.…”
Section: Spatial and Temporal Distribution And Changing Trend Of Anppsupporting
confidence: 92%
“…The alteration in ANPP is primarily induced by human activities and climate fluctuations. Numerous preceding studies have utilized ANPP, HNPP, and PNPP to differentiate these two elements' effects on ANPP [18,48,49,61,62,86]. Our research findings indicate that a combined influence of climate change and human activities has led to the increase in ANPP in the study area, with their combined effect being greater than the individual impacts of climate change or human activities on the vegetation's ANPP.…”
Section: The Relative Effects Of Climate Change and Human Activities ...mentioning
confidence: 63%
See 2 more Smart Citations
“…However, they did not specify which human activities dominated nor did they provide specific ecological restoration measures. Similarly, Zhou 26 , Xiong 27 , and Wang 28 studied the long-term trend of grassland ecosystems, emphasizing the positive role of human activities in grassland conservation. However, quantifying the contributions of various factors to grassland productivity remains a challenge.…”
Section: Introductionmentioning
confidence: 99%